Taiwan’s submarine debate : exploring alternative solutions - Koh, Collin Swee Lean (2011)
Debates over Taipei’s submarine acquisition plan have resurfaced in recent times. The plan is likely to continue to be dogged by intractable geopolitical, financial and technical hurdles. One possible alternative is to not